Impacts of Egg White Assisted Combustion and Ceramic Methods on Structural, Morphological and Magnetic Properties of Nickel Manganite System - Nasrallah Deraz; Omar Hamed Abd-Elkader; Mohamed Yassin (Crystals, 2020)
This study focuses on two different techniques for preparation of nickel manganite (NiMn2O4) system. One approach is conventional ceramic method, and the second is based on replacing the ceramic route with green synthesis mediated by egg white. The goal of this strategy is produce a single nanomagnetic phase of NiMn2O4 using a mostly simple one-step method with specific characteristics as seen in the second route compared to the ceramic method. The as synthesized system was characterized by using various techniques such as X-ray diffraction (XRD), scanning electron micrographs (SEM), and Energy dispersive X-ray spectrometry (EDS). XRD, EDS and SEM analyses confirm a successful synthesis of NiMn2O4 single phase with cubic spinel and sponge crystal structures. The particles are polycrystalline in their nature and average crystallite size ranged between 76 and 90 nm. Egg white assisted combustion method imparted amelioration in the system crystallization, size of grain, distribution of cation and magnetic properties of the as prepared materials. The magnetic mensuration suggested that the obtained nickel manganite shows ferromagnetism at room temperature with an optimum value (3.56 emu/g) of saturation magnetization.